Separating differential allocation by females from direct effects of male condition in a beetle. (25th March 2021) - Richardson, Jon; Smiseth, Per T
Abstract: Differential allocation is the adjustment of reproductive allocation, typically by a female, in response to the quality of her male partner. A recent theoretical model suggests that differential allocation may influence trade-offs between reproductive traits within a breeding attempt. Furthermore, it is often difficult to distinguish differential allocation from direct effects of male condition. We address these gaps using a novel cross-fostering design to exclude direct effects of male condition and to test whether differential allocation affects trade-offs between and within breeding attempts. This design detects differential allocation as effects of a female's mating partner and direct effects of male condition as effects of the larvae's sire. We used the burying beetle Nicrophorus vespilloides, a species which adjusts reproductive allocation by culling some larvae after hatching. We used food deprivation to manipulate the nutritional condition of both the female's mating partner and the larvae's sire. We find clear evidence for differential allocation as females mating with food-deprived males had fewer larvae than females mating with control males. There was a trade-off between number and size of larvae when females mated with control males, but a positive relationship when females mated with food-deprived males. Thus, differential allocation influenced relationships between reproductive traits within a breeding attempt, but not necessarily through trade-offs. Instead, we suggest that there may be cryptic heterogeneity in quality among females or their mating partners that was only exposed when females mated with a male in poor condition. Abstract : Female burying beetles had fewer larvae after mating with a food-deprived male. This shows that females adjust their reproductive allocation to the condition of their mate, a phenomenon known as differential allocation. Our experimental design excluded direct effects of male condition. Furthermore, there was a positive relationship between the number and size of larvae when females mated with a food-deprived male. Our results suggest that differential allocation could explain variation in life history trade-offs.